An introduction to organic chemistry - Brown, William H. (New York Harcourt College Pub, 1996)
This book enables readers to see the connections in organic chemistry and understand the logic. Reaction mechanisms are grouped together to reflect logical relationships. Discusses organic chemistry as it is applied to real-world compounds and problems. Electrostatic potential plots are added throughout the text to enhance the recognition and importance of molecular polarity. Presents problems in a new (3z(BLooking-Ahead(3y (Bsection at the end of each chapter that show how concepts constantly build upon each other. Converts many of the structural formulas to a line-angle format in order to make structural formulas both easier to recognize and easier to drs
Keywords: chemistry,organic chemistry